1985
DOI: 10.1111/j.2044-8309.1985.tb00678.x
|View full text |Cite
|
Sign up to set email alerts
|

Predicting our own aggression: Person, subculture or situation?

Abstract: Using a self-report technique, teenaged subjects (stratified by sex and social class) were asked to report their predicted behaviour over 24 conflict scenarios involving 12 male and 12 female targets. In terms of degree of aggression predicted, there was a strong effect of situation. Towards male targets, lower middle-class subjects were more aggressive than upper middle-class subjects and males were more aggressive than females. With respect to female targets, the social class difference again appeared but th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

1986
1986
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 12 publications
(15 reference statements)
0
14
0
Order By: Relevance
“…Violence or aggression among prison inmates is also predicted on the basis of situation variables. Steinke (1991) and Campbell et al (1985) found that the most powerful predictor of aggression in conflict scenarios was the situation being judged and not an aggressive personality. Still other examples abound in the literature.…”
Section: Symbolic Interaction Researchmentioning
confidence: 99%
“…Violence or aggression among prison inmates is also predicted on the basis of situation variables. Steinke (1991) and Campbell et al (1985) found that the most powerful predictor of aggression in conflict scenarios was the situation being judged and not an aggressive personality. Still other examples abound in the literature.…”
Section: Symbolic Interaction Researchmentioning
confidence: 99%
“…Knowledge of the interaction between the individual and environment is essential to an adequate description and understanding of behavior (Magnuson, 1981). Moreover, increased predictive power is found in behavior models that include environmental variables (Campbell, Bibel & Mincer, 1985). "Many stress researchers have overlooked the properties of physical situations most likely to place greater adaptive demands on human coping responses" (Evans & Cohen, 1987, p. 572).…”
Section: Influencing -> Appraisal Factors -> Outcomementioning
confidence: 99%
“…(1989) showed that boys expect less parental disapproval and less guilt to follow aggression. Campbell et al . (1985) found gender differences in the social representations held regarding aggression.…”
Section: Introductionmentioning
confidence: 99%